2004
DOI: 10.1021/ja031927c
|View full text |Cite
|
Sign up to set email alerts
|

Direct Determination of Hydrogen-Bonded Structures in Resonant and Tautomeric Reactions Using Ultrafast Electron Diffraction

Abstract: We elucidate the keto-enol tautomeric equilibrium in acetylacetone, the structure of both keto and enol forms, and the nature of the intramolecular O-H...O HB in enolic acetylacetone using our ultrafast electron diffraction apparatus, thereby shedding new light on the nature of the hydrogen bond in resonant tautomeric structures. The enolic structure exhibits some pi-resonance delocalization; however, this delocalization is not strong enough to give a symmetric skeletal geometry. The long O...O distance in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
111
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(128 citation statements)
references
References 31 publications
16
111
1
Order By: Relevance
“…In the ground state AA exhibits an asymmetric (C s ) structure (where the central H atom belongs to only one oxygen atom), and hence the geometry of the AA in the Franck−Condon region corresponds to an asymmetric structure where the H atom is closer to one of the oxygen atoms. 31 However, after the excitation, this asymmetry is broken as indicated by experimental and theoretical studies, 5,32−36 leading to a pseudoaromaticity. The 50 fs limit is very similar to the proton transfer rates of many related systems, e.g., o-hydroxybenzaldehyde, 1-hydroxy-2-acetonaphthone, methyl salicylate, 2-(2′-hydroxyphenyl)benzoxazole, and TINUVIN P. 37−40 With the time scale of τ 2 = 2.25 ps, the decrease of the ESA feature in the spectral range from 230 to 250 nm can be observed in the presented transients at 230 and 241 nm (confer Figure 3).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…In the ground state AA exhibits an asymmetric (C s ) structure (where the central H atom belongs to only one oxygen atom), and hence the geometry of the AA in the Franck−Condon region corresponds to an asymmetric structure where the H atom is closer to one of the oxygen atoms. 31 However, after the excitation, this asymmetry is broken as indicated by experimental and theoretical studies, 5,32−36 leading to a pseudoaromaticity. The 50 fs limit is very similar to the proton transfer rates of many related systems, e.g., o-hydroxybenzaldehyde, 1-hydroxy-2-acetonaphthone, methyl salicylate, 2-(2′-hydroxyphenyl)benzoxazole, and TINUVIN P. 37−40 With the time scale of τ 2 = 2.25 ps, the decrease of the ESA feature in the spectral range from 230 to 250 nm can be observed in the presented transients at 230 and 241 nm (confer Figure 3).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Nevertheless, electron diffraction results are contradictory [2,6,7], predicting a C s or a C 2v structure. A recent ultra fast electron diffraction study of Zewail et al [8] has demonstrated that, at least at the short timescale (~100 ps), the AA structure is asymmetrical with a d OO distance of 259 pm, 8 pm larger than the previous estimation [6]. The proton transfer barrier has been estimated at 6.6 kcal·mol -1 from the measured tunnelling splitting (21.6 cm -1 ) for MA [9][10][11], and besides, many theoretical studies have focussed on the description of this tunnelling process, trying to reproduce the measured splitting and to estimate the barrier height.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the formation of an intramolecular hydrogen bond in the protonated species is responsible for a significant enhancement of the intrinsic basicity of some acid anhydrides [8]. Finally, IHB's are crucial in many ultra-fast hydrogen transfer phenomena through the use of pulsed lasers [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%